Achievement of minimal disease activity in psoriatic arthritis according to the time of administration of synthetic disease-modifying antirheumatic drugs, a comparative analysis of the efficacy of oral and subcutaneous methotrexate. Data from the All-Russian Psoriatic Arthritis Registry - T. V. Korotaeva; E. Yu. Loginova; E. E. Gubar; Yu. L. Korsakova; M. V. Sedunova; I. N. Pristavsky; I. N. Kushnir; I. F. Umnova; S. S. Kudishina (Современная ревматология)
The goal of psoriatic arthritis (PsA) therapy is to achieve remission or minimal disease activity (MDA). According to the EULAR guidelines, synthetic disease-modifying antirheumatic drugs (sDMARDs), methotrexate (MTX) in particular, are first-line therapy for PsA.Objective: to study the rate of MDA achievement after initiation of sDMARD therapy in patients with early- and late-stage PsA and the efficacy of oral and parenteral MTX.Patients and methods. The investigation enrolled 253 patients (93 men and 160 women) diagnosed with PsA who met the appropriate 2006 CASPAR (ClASsification criteria for Psoriatic ARthritis) criteria and were recorded in the All-Russian PsA Registry. The median (Me) age was 47 (Min 20 – Max 82) years. All the patients took sDMARDs: MTX (n=211) that was received orally (as tablets) (n=102) and parenterally (n=109); leflunomide (n=7); sulfasalazine (n=24); apremilast (n=10); and tofacitinib (n=1). According to the disease duration at sDMARD treatment initiation, the patients were divided into two groups. Group 1 included 165 patients with an early PsA duration of less than 2 years and Group 2 consisted of 88 patients with a disease duration of >2 years. The efficiency of oral and parenteral MTX was evaluated in 182 patients (68 men and 114 women). Every 6 months, the patients underwent a standard rheumatology examination that included PsA activity assessment. The efficiency of MTX therapy was evaluated from MDA achievement (5 out of the 7 criteria) in the patients.Results and discussion. After sDMARD prescription, MDA was achieved in 39 (24%) of the 165 patients with early PsA and in 4 (5%) of the 88 long-term patients. The patients who started sDMARD at an early stage of the disease were significantly more likely to achieve MDA than those with late-stage PsA (odds ratio (OR) 6.5; 95% confidence interval (CI) 2.2–18.9). At 11 years after sDMARD therapy initiation, the cumulative MDA achievement rate in the patients with late-stage disease was 5% (p<0.05). MDA was achieved by 16.5% of the 182 patients receiving oral or subcutaneous MTX. MDA was observed in 25 (31%) patients who received parenteral MTX and in only 5 (5%) patients who took oral MTX. The patients who received parenteral MTX were significantly more likely to achieve MDA than those who took oral MTX as tablets (OR 8.8; 95% CI 3.2–24.3). Following 27-month parenteral MTX therapy, the cumulative rate of MDA achievement was 48%, whereas after oral MTX treatment, that was 7% (p<0.05). In the patients who achieved MDA, the mean dose of parenteral MTX was 17 mg/week, and in those who failed, that was 15 mg/week. The mean dose of oral MTX was 15 mg/week, regardless of MDA achievement.Conclusion. The administration of sDMARD at an early stage of PsA lasting less than 2 years allows MDA to be achieved significantly more often and faster than at later stages of the disease. Among sDMARDs, preference is mostly given to the use of MTX in real clinical practice; the treatment with the latter enables 16.5% of patients to achieve MDA. Parenteral MTX significantly enhances the efficiency of therapy and can achieve MDA in almost one third (31%) of patients.